PENGARUH MODAL INTELEKTUAL TERHADAP PROFITABILITAS PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Caroline, Annauly Maria; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the effect of the performance of intellectual capital consisting of value added physical capital (VACA), value added human capital (VAHU), stuctural capital value added (STVA), and value added intellectual coefficient (VAIC) on the company’s profitability as measured by return  on equity (ROE) and return on asset (ROA). The data used is the manufacturing companies listed in Indonesian Stock Exchange (IDX) 2011-2013. This empirical study using PLS (Partial Least Squares) as an analysis of the relationship between intellectual capital  (VAIC)  on manufacturing company’s  profitability. The analysis showed that: (1) intellectual capital (VAIC) positive and significant effect on the company’s profitability, (2) intellectual capital (VAIC) positive and significant effect on the company’s profitability of the future, and (3) the rate of growth of intellectual capital (ROGIC) positive and significant effect on the company’s profitability of the future.